PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KESEHATAN MENTAL KARYAWAN DI SEKTOR INDUSTRY RETAIL STUDI PADA KARYAWAN ALFAMART DI PAMULANG - Nico Septian Fazri Suparno; Yola Aulia Sulistiawati; Betran Febriansyah; Syaepul Anwar (Journal of Research and Publication Innovation, 2025)
This research aims to determine the effect of workload and work environment on the mental health of employees in the retail industry sector. This research was conducted on employees at PT. Alfamart. This research used a quantitative method by distributing question questionnaires while the research sample was carried out using simple random sampling, data collection with field studies to 23 employees at PT. Alfamart. Statistical data analysis uses normality test, coefficient determination, t test, f test with SPSS statistical tools. The research results show that workload has no effect on employee mental health. This is because there is cooperation and awareness to help each other in employee operations so that the workload does not put pressure on employees to the point that they experience stress or mental health problems. Meanwhile, the work environment influences employee mental health. A conducive work environment, both physically and psychologically, can motivate employees so they can provide their best performance and thus avoid mental health problems.